Dental Caries Severity and Nutritional Status of Nigerian Preschool Children. (April 2022) - Olatosi, O.O.; Alade, A.A.; Naicker, T.; Busch, T.; Oyapero, A.; Li, M.; Pape, J.; Olotu, J.; Awotoye, W.; Hassan, M.; Adeleke, C.; Adeyemo, W.L.; et al.
Introduction: Malnutrition in children is one of the most prevalent global health challenges, and malnourished children have a higher risk of death from childhood diseases. Early childhood caries (ECC) is the most common chronic disease of childhood. Complications from ECC such as pain, loss of tooth/teeth, and infection can undermine a child's nutrition and growth. Aim: This study aims to evaluate the severity of decay, missing, and filled tooth (dmft) by nutritional status using the z scores of the anthropometric measurements: height for age (HFA), weight for age (WFA), weight for height (WFH), and body mass index for age (BMIA) among children with ECC in Nigeria. Study Design: This is a cross-sectional study conducted in 5 local government areas (LGAs) in Lagos State, Nigeria. A multistage sampling technique was used. Results: A total of 273 cases of ECC were included in the analyses (mean age 4.19 ± 0.96 y). Overall, the mean dmft was 3.04 ± 2.28, and most (96%) were accounted for by untreated decay. The distribution of dmft within the different z score categories of BMIA (<–3 = severely wasted, –2 to –3 = wasted, –2 to +2 = normal, +2 to +3 = overweight and >+3 = obese) showed the highest dmft scores among the combined severely wasted and wasted groups, lowest among children with normal z scores, and intermediate in the overweight and obese groups. There was a significant negative correlation between BMIA z score, WFH z score, and dmft ( r = −0.181, P < 0.05 and r = −0.143, P < 0.05, respectively). However, the correlations between HFA z score, WFA z score, and dmft were positive but not significant ( r = 0.048, P = 0.44 and r = 0.022, P = 0.77, respectively). Conclusion: Our study showed an increased severity of dental caries among severely wasted or wasted children with ECC compared to those of normal or overweight. Knowledge Transfer Statement: The results from this study will raise awareness among clinicians and policy makers on the need for a primary prevention program for early childhood caries in countries with high burden of malnutrition and limited resources. Also, it will help draw the attention of clinicians to the caries status of malnourished children that can be managed to improve the nutritional outcomes.